2008
DOI: 10.1371/journal.pone.0003962
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms within the Novel Type 2 Diabetes Risk Locus MTNR1B Determine β-Cell Function

Abstract: BackgroundVery recently, a novel type 2 diabetes risk gene, i.e., MTNR1B, was identified and reported to affect fasting glycemia. Using our thoroughly phenotyped cohort of subjects at an increased risk for type 2 diabetes, we assessed the association of common genetic variation within the MTNR1B locus with obesity and prediabetes traits, namely impaired insulin secretion and insulin resistance.Methodology/Principal FindingsWe genotyped 1,578 non-diabetic subjects, metabolically characterized by oral glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
98
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 36 publications
17
98
0
Order By: Relevance
“…In agreement with our result, a previous study showed an association between a different SNP and decreased HOMA-IR [34]. In contrast, a study based on the hyperinsulinaemic-euglycaemic clamp showed that the MTNR1B risk allele reduced suppression of hepatic glucose production, suggesting that it could be associated with hepatic IR [35].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our result, a previous study showed an association between a different SNP and decreased HOMA-IR [34]. In contrast, a study based on the hyperinsulinaemic-euglycaemic clamp showed that the MTNR1B risk allele reduced suppression of hepatic glucose production, suggesting that it could be associated with hepatic IR [35].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a polymorphic allele was identified in CRY2 associated with type 2 diabetes (85). A group of researchers reported that the MTNR1B-associated Single Nucleotide Polymorphisms rs10830962, rs4753426 and the aforementioned rs10830963 were all significantly associated with higher fasting glucose concentrations in the blood and decreased insulin secretion in German cohorts (86).…”
Section: Melatonin Receptor Polymorphismmentioning
confidence: 99%
“…Moreover, diabetes is coupled with lower melatonin levels as reduction in serum melatonin and higher insulin level is observed in type 2 diabetic Goto Kakizaki rats (6). Genome-wide association studies has shown that specific single-nucleotide polymorphisms of the melatonin receptor 2 (MTNR1B) locus is linked with an increased blood glucose concentration and type 2 diabetes (8)(9)(10)(11)(12)(13). Melatonin can be able to bring anti-hyperglycemic effect either by improving insulin sensitization or by improvement of insulin secretion, or both.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, common variants in melatonin receptor type 1 B gene (MTNR1B) are associated with the risk of T2D independent of BMI [34,35]. Receptors for melatonin (MTNR1A and MTNR1B) are expressed in pancreatic islet cells, and carriers of the risk genotype exhibit impaired glucose-stimulated insulin secretion [36,37].…”
Section: Type 2 Diabetes and Obesity -Genetic Tiesmentioning
confidence: 99%